Intracellular Na+ modulates the cAMP-dependent regulation of ion channels in the heart. - Harvey, R D (1991)
The cAMP-dependent regulation of ion channels was studied by using the whole-cell configuration of the patch clamp technique. In isolated cardiac ventricular myocytes, the beta-adrenergically regulated Cl- current (ICl) exhibited an unusual dependence on Na+, such that replacement of extracellular Na+ with compounds such as tetramethylammonium, choline, Tris, or N-methyl-D-glucamine resulted in a reduction in current amplitude without changing the reversal potential. Replacement of extracellular Na+ with tetramethylammonium also reduced the magnitude of the beta-adrenergically enhanced Ca2+ current and delayed rectifier K+ current, suggesting that removal of Na+ was affecting the cAMP pathway that regulates all three currents. Replacement of extracellular Na+ also reduced ICl that was stimulated by (i) direct activation of adenylate cyclase with forskolin, (ii) inhibition of phosphodiesterase with 3-isobutyl-1-methylxanthine, (iii) exposure to the membrane-permeable cAMP derivative 8-bromoadenosine 3',5'-cyclic monophosphate, or (iv) direct phosphorylation of the channel with protein kinase A catalytic subunit. This suggests that the Na+ dependence is at a point beyond the activation of protein kinase A. The Na+ dependence of ICl regulation could not be explained by changes in intracellular Ca2+. However, the sensitivity of the ICl to changes in extracellular Na+ depended significantly on the intracellular Na+ concentration, suggesting that intracellular Na+ plays an important role in the cAMP-dependent regulation of ion channels.